2020
DOI: 10.1037/int0000220
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of a telepsychotherapy parenting skills intervention for veteran families: Implications for managing parenting stress during COVID-19.

Abstract: Changes in daily life created by the novel coronavirus (COVID-19) pandemic have resulted in a largely unprecedented situation for millions of families worldwide. Families are under considerable stress, and parents may experience greater psychological distress and disruptions in the parent-child relationship. Some parents may be particularly vulnerable to recent stressors, including those with preexisting psychological disorders and family dysfunction. In the United States, military veterans are one such at-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 37 publications
2
61
0
6
Order By: Relevance
“…Future follow-up studies in this cohort can document how the pandemic might contribute to changes in family and parenting dynamics. At the same time, the pandemic has galvanized researchers and practitioners towards online interventions to promote effective parenting [ 81 ], which may be particularly helpful to reduce child CP and CU traits. Indeed, a recent meta-analysis of 12 studies found that online parenting programs are effective in reducing child CP and improving parental mental health problems [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future follow-up studies in this cohort can document how the pandemic might contribute to changes in family and parenting dynamics. At the same time, the pandemic has galvanized researchers and practitioners towards online interventions to promote effective parenting [ 81 ], which may be particularly helpful to reduce child CP and CU traits. Indeed, a recent meta-analysis of 12 studies found that online parenting programs are effective in reducing child CP and improving parental mental health problems [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…We encourage policy makers to focus on families as an important societal functional unit. Initial support for burdened parents is urgently needed at all levels to mitigate the negative impact of COVID-19 on mental health in parents and children by providing public health education [ 113 ], offering positive parenting training and psychological support via telehealth [ 114 , 115 ], providing funding to mitigate economic hardship [ 116 ], strengthening couple relationships, and promoting general family functioning for building resilience [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promising approaches have included (a) the use of webinars and other parent-paced learning tools ( DuPaul et al., 2018 ) and (b) individualized therapy using telepsychology ( Gurwitch et al., 2020 ; Sibley et al., 2017 ). Recent research has further illustrated that individualized BPT can be delivered effectively in other populations experiencing similar needs (e.g., parenting-related stress, Riegler et al., 2020 ; family adjustment to neurological conditions, Wade et al., 2020 ). Emerging evidence also supports implementation of group parenting interventions using telepsychology ( Reese et al., 2015 ; Xie et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%